Development of Laboratory Skills Application Based on Android as a Media of Flipped Learning Model for Nursing Student - Buhari, Basok; Sari, Rian Maylina (The Malaysian Journal of Nursing (MJN), 2022)
The development of the current era is closely related to the increase in digitalization. The impact of the development of digitalization has a positive effect on the field of education. Online learning using digitalization changes learning models that tend to be passive to active through the management of learning models in the classroom or laboratory based on digital media. The research design was development method which was adapted from the 4D model (Four D Model) which consists of four stages, namely: define, design, development, and dissemination. The data type of this research is quantitative data. Quantitative data is obtained from scores from experts and nursing student as user. The data type of this research is quantitative data. Quantitative data is obtained from scoring scores from experts and nursing student as user. This research was conducted at Nursing Study Program, Sekolah Tinggi Ilmu Kesehatan Harapan Ibu Jambi, Jambi Province, Indonesia. The results of media on experts learning applications get a percentage 96.25%. These percentage can be interpreted as application of dissemination media and is very decent to use. The results by design experts, overall learning application get a percentage 85.2%, with these percentage can be interpreted as application of dissemination media is very decent to use. The results of the attractiveness test show that nursing student respond very well to the use of Android as a learning media for flipped learning models. Nursing student consider the packaging of material in the form of material, procedural, learning videos and article, as well as the interactivity and ease of use of these media to make material about skills laboratory more interesting to study.